Tactics of Treatment of Fractures of Tubular Bones - Topvoldiev Saydillo Abduraxmonovich (Genius Journals, 2023)
The growth of traffic flows, industry, as well as changes in the socio-spiritual life of society lead to an increase in the frequency and severity of injuries. In this article highlights tactics of treatment of fractures of tubular bones.
Keywords: medicine; tactics of treatment; patient